Exploring the challenges of clinical education in nursing and strategies to improve it: A qualitative study - Saba Farzi; Mohsen Shahriari; Sedigheh Farzi (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Clinical education is the heart of professional education in nursing. The perspective of nursing students and clinical nursing educators as the main owners of teaching-learning process are of determinants affecting clinical education process. This study was conducted to explore and to describe the clinical education problems and strategies to improve it from the perspective of nursing students and clinical nursing educators. MATERIALS AND METHODS: The study was conducted using a descriptive qualitative method in 2017. Participants included 35 baccalaureate nursing students and 5 clinical nursing educators from nursing faculty of Isfahan University of Medical Sciences, Isfahan, Iran. Participants were selected using purposeful sampling method. Data were collected through semi-structured individual interviews and used qualitative content analysis for analysis. RESULTS: The 2 main categories, 7 subcategories, and 19 sub-sub categories extracted from interviews. The two categories were "challenges of clinical education in nursing with four subcategories: fear, insufficient readiness of student, incompetency of clinical educators, unpleasant atmosphere of clinical environment," and "strategies for improving clinical education of nursing with three subcategories: the use of nursing education models and methods, improvement of communication between faculty and practice, and holding orientation stage at the beginning of training." CONCLUSIONS: The findings show that clinical strategies, including employing experienced clinical educators, attempting to enhance the learning environment, developing the relationship between faculty and practice, participation of clinical nurses in clinical education, paying attention to entering behavior, and holding orientation stage at the beginning of training, can improve clinical education of nursing.